Reference dependent preferences and the impact of wage increases on job satisfaction: theory and evidence - Christian Grund; Dirk Sliwka (Institute for the Study of Labor (IZA), 2005)
The impact of wage increases on job satisfaction is explored theoretically and empirically. To do this, we apply a utility function that rises with the absolute wage level as well as with wage increases. It is shown that when employees can influence their wages by exerting effort, myopic utility maximization directly implies increasing and concave shaped wage profiles. Furthermore, employees get unhappier over time staying on a certain job although wages increase. Using data from 19 waves of the German Socio-Economic Panel we find empirical support for both the form of the utility function and the decreasing job satisfaction patterns.
Keywords: M54; J28; J30; M12; 330; job satisfaction; wage increases; wage profiles; reference dependent utility; habit formation; loss aversion; Lohnniveau; Leistungsmotivation; Nutzenfunktion; Panel; Schätzung; Deutschland